Dynamic control of X-ray core-exciton resonances by Coulomb screening in photoexcited semiconductors - Thomas C. Rossi; Lu Qiao; Conner P. Dykstra; Ronaldo Rodrigues Pela; Richard Gnewkow; Rachel F. Wallick; John H. Burke; Erin Nicholas; Anne Marie March; Gilles Doumy; D. Bruce Buchholz; Christiane Deparis; et al. (Communications Materials)
Abstract Excitonics is an emerging field focused on exploiting and manipulating excitons generated through light-matter interactions. Advancing the field into X-ray excitonics requires precise energy and time control of core-exciton resonances, enabling non-linear X-ray phenomena such as element-specific X-ray transient gratings, and advancing material characterization. To achieve these objectives, it is essential to comprehend the role of many-body effects governing core-exciton dynamics. In this work, we address this challenge by combining experiments with an ab initio approach specifically developed to interpret pump-probe excitations. Applied to the prototypical wide-bandgap semiconductor ZnO, first-principles calculations reproduce experimental results and unveil how the density and distribution of photoexcited carriers dynamically tune Coulomb screening, thereby controlling core-exciton binding energies, while Pauli blocking remains negligible. These insights inform a method for dynamically controlling core-exciton resonances at absorption edges, achieving either a uniform spectral blue shift caused by thermalized carrier distributions on picosecond timescales, or distinct blue shifts for individual resonances, driven by time-dependent carrier distributions on femtosecond timescales.